2016
DOI: 10.1016/j.jcmgh.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Enterohemorrhagic Escherichia coli Reduces Mucus and Intermicrovillar Bridges in Human Stem Cell-Derived Colonoids

Abstract: BACKGROUND AND AIMS Enterohemorrhagic E. coli (EHEC) causes over 70,000 episodes of foodborne diarrhea annually in the USA. The early sequence of events which precede life-threatening hemorrhagic colitis and hemolytic uremic syndrome are not fully understood due to the initial asymptomatic phase of the disease and the lack of a suitable animal model. The aim of this study was to determine the initial molecular events in the interaction between EHEC and human colonic epithelium. METHODS Human colonoids derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
259
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 218 publications
(270 citation statements)
references
References 41 publications
10
259
1
Order By: Relevance
“…The development of nontransformed human intestinal epithelial cell cultures that model intestinal biology (2) has stimulated interest in new studies of host-pathogen interactions, with most recently reported studies focusing on bacterial infections (1,7,(49)(50)(51)64). Here, we demonstrate the utility of such novel ex vivo multicellular, physiologically active cultures to study a human enteric virus (HRV) to gain new insight into interactions with human small intestinal cells in cultures established from different patients.…”
Section: Discussionmentioning
confidence: 95%
“…The development of nontransformed human intestinal epithelial cell cultures that model intestinal biology (2) has stimulated interest in new studies of host-pathogen interactions, with most recently reported studies focusing on bacterial infections (1,7,(49)(50)(51)64). Here, we demonstrate the utility of such novel ex vivo multicellular, physiologically active cultures to study a human enteric virus (HRV) to gain new insight into interactions with human small intestinal cells in cultures established from different patients.…”
Section: Discussionmentioning
confidence: 95%
“…Although this discussion has focused on inflammatory bowel disease and graft-versus-host disease, which has been studied extensively, other examples of disease-associated gut barrier loss abound, including those that occur within the contexts of intestinal infection (Halliez et al, 2016;In et al, 2016;Zolotarevsky et al, 2002), irritable bowel syndrome (Bertiaux-Vandaële et al, 2011;Martínez et al, 2013;Wu et al, 2016), celiac disease (Schumann et al, 2012;Setty et al, 2015;Szakál et al, 2010) and environmental enteric dysfunction (Kelly et al, 2016;Vinetz et al, 2016;Yu et al, 2016). Although studied to a lesser extent, barrier defects also occur in pulmonary, renal and dermatologic diseases.…”
Section: Isolated Tight Junction Dysfunction Is Insufficient To Causementioning
confidence: 99%
“…Is Reproducible Across HIEs from Different People. HIEs are novel, physiologically active, nontransformed cultures that are increasingly used to study human pathogen-host interactions (5,8,9,39,40). We first evaluated the variability in the transcriptional response to HRV infection in HIEs by analyzing transcriptomes from one jejunal HIE culture by microarray analysis.…”
Section: Significancementioning
confidence: 99%